Comparative Expression Analysis of Stress-Inducible Candidate Genes in Response to Cold and Drought in Tea Plant [Camellia sinensis (L.) Kuntze] - Samarina, Lidiia S.; Bobrovskikh, Alexandr V.; Doroshkov, Alexey V.; Malyukova, Lyudmila S.; Matskiv, Alexandra O.; Rakhmangulov, Ruslan S.; Koninskaya, Natalia G.; Malyarovskaya, Valentina I.; Tong, Wei; Xia, Enhua; Manakhova, Karina A.; Ryndin, Alexey V.; et al. (Frontiers in Genetics, 2020)
Cold and drought are two of the most severe threats affecting the growth and productivity of the tea plant, limiting its global spread. Both stresses cause osmotic changes in the cells of the tea plant by decreasing their water potential. To develop cultivars that are tolerant to both stresses, it is essential to understand the genetic responses of tea plant to these two stresses, particularly in terms of the genes involved. In this study, we combined literature data with interspecific transcriptomic analyses (using Arabidopsis thaliana and Solanum lycopersicum) to choose genes related to cold tolerance. We identified 45 stress-inducible candidate genes associated with cold and drought responses in tea plants based on a comprehensive homologous detection method. Of these, 9 were newly characterized by us, and 36 had previously been reported. The gene network analysis revealed upregulated expression in ICE1-related cluster of bHLH factors, HSP70/BAM5 connected genes (hexokinases, galactinol synthases, SnRK complex, etc.) indicating their possible co-expression. Using qRT-PCR we revealed that 10 genes were significantly upregulated in response to both cold and drought in tea plant: HSP70, GST, SUS1, DHN1, BMY5, bHLH102, GR-RBP3, ICE1, GOLS1, and GOLS3. SnRK1.2, HXK1/2, bHLH7/43/79/93 were specifically upregulated in cold, while RHL41, CAU1, Hydrolase22 were specifically upregulated in drought. Interestingly, the expression of CIP was higher in the recovery stage of both stresses, indicating its potentially important role in plant recovery after stress. In addition, some genes, such as DHN3, bHLH79, PEI54, SnRK1.2, SnRK1.3, and Hydrolase22, were significantly positively correlated between the cold and drought responses. CBF1, GOLS1, HXK2, and HXK3, by contrast, showed significantly negative correlations between the cold and drought responses. Our results provide valuable information and robust candidate genes for future functional analyses intended to improve the stress tolerance of the tea plant and other species.